2019
DOI: 10.3390/agronomy9070341
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Straw Incorporation Rate on Water–Salt Balance and Maize Yield in Soil Subject to Secondary Salinization with Brackish Water Irrigation

Abstract: Secondary salinization induced by brackish water irrigation has forced agricultural development to increasingly rely on soil management. A two-year field experiment was conducted to explore the effects of different straw incorporation rates (SIRs) within 0 to 20 cm topsoil on the soil water–salt balance, maize yield production, and water use efficiency (WUE) under brackish water irrigation in a naturally non-saline area. Air-dried wheat straw was applied at the rates of 0, 4.5, 9.0, 13.5, and 18.0 t ha−1 (R0–R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…As Figure 1 indicated, within the soil depth of 0-20 cm, the soil moisture content under L1 and L2 had greater values than that under CK during each stage of maize growth in 2017. The results in the present study were in agreement with the previous studies, which found that the soil moisture of the cultivated layer could be increased due to straw incorporation [39]. For example, the soil moisture content within 0-20 cm was 17.37%, 10.10% and 4.79% higher under L1, L2 and L3 than that under CK on average in 2017.…”
Section: Dynamics Of Soil Moisturesupporting
confidence: 93%
See 2 more Smart Citations
“…As Figure 1 indicated, within the soil depth of 0-20 cm, the soil moisture content under L1 and L2 had greater values than that under CK during each stage of maize growth in 2017. The results in the present study were in agreement with the previous studies, which found that the soil moisture of the cultivated layer could be increased due to straw incorporation [39]. For example, the soil moisture content within 0-20 cm was 17.37%, 10.10% and 4.79% higher under L1, L2 and L3 than that under CK on average in 2017.…”
Section: Dynamics Of Soil Moisturesupporting
confidence: 93%
“…For all treatments, with the continuous irrigation of brackish water, the salinity in the soil has been accumulated at a fairly high level. Compared with the deeper soil, the salt accumulation in the 0-20 cm soil layer in each treatment was more obvious, which has been confirmed by the previous study [39]. Similar patterns were found in 2018, but the SAR of 0-20 cm (5.77, 7.04, 9.15 and 10.43) were obviously lower than that in 2017, and the effects of different lengths of straw incorporated into cultivated fields on soil salinity was more visible, which was likely induced by the impact of continuous straw incorporation [45].…”
Section: Variations Of Soil Salinitysupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, Levy [44] and Zheng et al [45] reported that brackish water can decrease crop growth and yield, as salt damage makes it difficult for plant roots to absorb water. However, Lu et al [46] showed that applying brackish water increased corn yield and WUE under high crop residue return conditions. Therefore, long-term studies regarding the impacts of crop residue on crop yields under brackish irrigation are needed to identify effective methods of such irrigation.…”
Section: Plos Onementioning
confidence: 98%
“…The findings of this study indicated that the nitrification process in soil amended with urea was slowed by the application of P fertilizer, indicating that a synergistic feature of N and P nutrient management should be further investigated to slow N losses from agricultural systems. Furthermore, the most frequently form of nitrogen or sulfur fertilizer in soil is nitrates or sulfate (S) (Brito et al, 2007;Vandenberghe et al, 2012), which is likely to exacerbate secondary salinization in the soil layer (Lu et al, 2019;Shen et al, 2016). Increased secondary salinization may lead to a reduction in soil fertilizer availability, which would reduce the productivity of crops, like cotton (Osanai et al, 2017;Tian et al, 2018), sunflower (Aziz et al, 2019), and maize (Lu et al, 2019;Rajeshwar & Khan, 2010).…”
Section: Fertilizer Practice Changesmentioning
confidence: 99%